2003
DOI: 10.1103/physrevlett.91.205503
|View full text |Cite
|
Sign up to set email alerts
|

Helical Gold Nanotube Synthesized at 150 K

Abstract: Gold nanowires were synthesized at 150 K by electron beam thinning of a gold thin foil in an UHV electron microscope. The gold nanowires were found to have a helical multishell structure (HMS). One particular nanowire, which was thinner than the 7-1 HMS nanowire, was found to have a tubular structure. The gold single wall nanotube is composed of five atomic rows that coil about the tube axis. The diameter was 0.4 nm and the pitch was 11 nm. The stability of the (5,3) nanotube was discussed in terms of the shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
191
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(211 citation statements)
references
References 39 publications
15
191
0
1
Order By: Relevance
“…The obtained fully relaxed structure parameters are shown in Table I too, and from it we can find that the diameter of the shear-strain deformed SWGT (5, 3) is only slightly larger than that of the perfect one. But its binding energy per gold atom is smaller than that of perfect tube by 0.008 eV, which means it is more stable than the perfect tube, being consistent with the experimentally observed result [11]. Its calculated electronic band structures and DOSs are shown in Fig.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The obtained fully relaxed structure parameters are shown in Table I too, and from it we can find that the diameter of the shear-strain deformed SWGT (5, 3) is only slightly larger than that of the perfect one. But its binding energy per gold atom is smaller than that of perfect tube by 0.008 eV, which means it is more stable than the perfect tube, being consistent with the experimentally observed result [11]. Its calculated electronic band structures and DOSs are shown in Fig.…”
supporting
confidence: 77%
“…It is found that the inner and outer shells always have even-odd or odd-even coupling, and the difference (n − n ′ ) between their number of atomic row is equal to seven (a single atom chain is regarded as "0"-membered in this discussion). Nanowires with n ≤ 6 had been supposed to have only a single-walled shell [7], called as SWGT, which has recently been synthesized experimentally at 150 K in an UHV-TEM [11]. The thinnest SWGT, 4 A in diameter, was found to be the (5, 3), composed of five atomic rows coiled round the tube axis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments [1][2][3][4] indicate that gold nanowires exhibit fascinating ordered structures that resemble those of the by now well-known carbon nanotubes ͑CNTs͒. 5 High resolution microscope images show that these wires consist of coaxial nanotubes of helical atom rows coiled around the wire axis.…”
Section: Introductionmentioning
confidence: 99%
“…So single-walled nanotubes should exist with six or less atom rows, and actually one single-walled tube with five atom rows has been observed. 3 With seven or more atom rows a double-walled tube should be seen, which becomes a triple-walled nanotube when more than fourteen rows are present, and so on. The good reproducibility of these wires, and their stability, [6][7][8][9] which is better for those with outer tubes with an odd number of atom rows, makes them promising candidates for future applications.…”
Section: Introductionmentioning
confidence: 99%